RANCANGAN APLIKASI SISTEM PENGELOLAAN ORDERAN PADA TOKO L.DAY'S LAUNDRY - Arya Kusuma Wardhana; Ara Dwi Nata; Rama Andika (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Technological developments change the management of the inventory system which is still done manually to become computerized. There are many benefits from the results of computerized order data management for companies, including the L.Day's Laundry Store. existing data in the bookkeeping, making it difficult to know the details of customer transactions. Based on the description stated above, the researcher wants to provide a solution by making Java and PHP-based programs. We have made observations at the L.Day's Laundry shop which is located on Jl. Education, Cibadung, Kec. mt. Sindur, Bogor Regency, West Java 16340 to find out the organizational structure and activities that have been running or are currently running at the L.Day's Laundry Shop. From interviews conducted with the L.Day's Laundry Shop Owner. The problem that must be solved is to manage orders in a computerized manner. Therefore, researchers need a Java-based Order Management System and a website to make it easier to manage orders.